Non-invasive assessment of cardiac output in children. Issue 5 (September 1998) - Richardson, J R; Ferguson, J; Hiscox, J; Rawles, J
Abstract : BACKGROUND: Stroke distance, the systolic velocity integral of aortic blood flow, is a linear analogue of stroke volume; its product with heart rate is minute distance, analogous to cardiac output. OBJECTIVE: To investigate the feasibility of assessing cardiac output in children with a simple non-invasive Doppler ultrasound technique, and to determine the normal range of values. METHODS: Peak aortic blood velocity, stroke distance, and minute distance were measured through the suprasternal window in 166 children (mean age 9.6 years, range 2-14) using a portable non-imaging Doppler ultrasound instrument. RESULTS: The technique was well tolerated by all the children participating. Mean peak aortic blood velocity was 138 cm/s and was independent of age. Mean stroke distance was 31.8 cm and showed a small but significant increase with age; mean minute distance was 2490 cm and fell with age, as did heart rate. CONCLUSIONS: Suprasternal Doppler ultrasound measurement of stroke distance is a convenient, well tolerated, non-invasive technique for the assessment of cardiac output in children. The normal range of values during childhood has been established. The technique has great potential for assessing hypovolaemia in children.